Efficacy and Safety of Low Dose Thalidomide in Transfusion Dependent Thalassemia Patients: A Preliminary Study - Masood Khan, Muhammad Tariq (International Journal of Pathology, 2022)
Background: Thalidomide is known to have hypnosedative, immuno-modulatory and anti-angiogenic effects. The drug is widely used in several neoplastic disorders, inflammatory conditions and skin disorders. Thalidomide has been successfully used in limited number of adult thalassemia patients. Studies on younger thalassemia patients are lacking.Objective: Current study aims at exploring efficacy and safety profile of thalidomide in younger thalassemia patients.Methods: A cohort of 20 randomly selected transfusion dependent thalassemia patients were enrolled into the study. Base-line clinico-haematological and biochemical parameters were recorded for each patient. All the patients were given thalidomide for a period of six months and the response was recorded on monthly basis. Data collected was analysed for statistical significance. Study patients included 16 male and 4 female patients.Results: Mean age of study patients was 12.8 ± 3.6 years. Mean haemoglobin (Hb) levels, pre and post thalidomide, were 4.8 (±1.5) g/dL and 8.2 (±1.8) g/dL respectively (p-value <0.05). Among study patients, 8 (40%) showed Excellent Response, 7 (35%) showed Good Response, 3 (15%) had Poor Response while 2 (10%) patients did not respond to the treatment. No major side effects of therapy were observed among study patients.Conclusion: The study concludes that thalidomide significantly raises Hb levels in transfusion dependent thalassemia patients when given in low doses. Safety profile for usage of thalidomide in this group of patients is satisfactory.Trial Registration: NCT03651102, https://clinicaltrials.gov/ct2/show/NCT03651102